Nosocomial infections due to methicillin-resistant Staphylococcus aureus and vancomycin-resistant enterococci at a university hospital in Taiwan from 1991 to 2003: resistance trends, antibiotic usage and in vitro activities of newer antimicrobial agents - Hsueh, Po-Ren (Int J Antimicrob Agents, 2005)
A rapid increase of nosocomial methicillin-resistant Staphylococcus aureus (MRSA) infection (from 39% in 1991 to 75% in 2003) and vancomycin-resistant enterococci (VRE) (from 1.2% in 1996 to 6.1% in 2003) at a university hospital in Taiwan was found. The noticeable rise of MRSA and VRE was significantly correlated with the increased consumption of glycopeptides, β-lactam–β-lactamase inhibitor combinations, extended-spectrum cephalosporins, carbapenems and fluoroquinolones (Pearson's correlation coefficient, P < 0.05). Minimum inhibitory concentrations (MICs) of 100 non-duplicate blood isolates of MRSA (in 2003) and of 25 non-duplicate isolates of vancomycin-resistant Enterococcus faecalis and 172 vancomycin-resistant Enterococcus faecium (in 1996–2003) causing nosocomial infection recovered from various clinical specimens of patients treated at the hospital to nine antimicrobial agents were determined by the agar dilution method. All of these isolates were susceptible to linezolid and were inhibited by 0.5 mg/L of tigecycline, and all MRSA isolates were inhibited by daptomycin 1 mg/L, including two isolates of MRSA with heteroresistance to vancomycin. Daptomycin had two-fold better activity against vancomycin-resistant E. faecalis (MIC(90), 2 mg/L) than against vancomycin-resistant E. faecium (MIC(90), 4 mg/L). Decreased susceptibilities of vancomycin-resistant E. faecium and MRSA to quinupristin/dalfopristin (non-susceptibility 25% and 8%, respectively) were found. Telithromycin had poor activity against the isolates tested (MIC(90), 8 mg/L). Linezolid, daptomycin and tigecycline may represent therapeutic options for infections caused by these resistant Gram-positive organisms.